2021
DOI: 10.3390/biomedicines9101324
|View full text |Cite
|
Sign up to set email alerts
|

Mambalgin-2 Inhibits Growth, Migration, and Invasion of Metastatic Melanoma Cells by Targeting the Channels Containing an ASIC1a Subunit Whose Up-Regulation Correlates with Poor Survival Prognosis

Abstract: Melanoma is an aggressive cancer characterized by the acidification of the extracellular environment. Here, we showed for the first time that extracellular media acidification increases proliferation, migration, and invasion of patient-derived metastatic melanoma cells and up-regulates cell-surface expression of acid-sensitive channels containing the ASIC1a, α-ENaC, and γ-ENaC subunits. No influence of media acidification on these processes was found in normal keratinocytes. To control metastatic melanoma prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Melanoma growth is accompanied by acidification of the tumor microenvironment to pH ~6.5 instead of ~7.4 in normal conditions [30]. Acidification of the microenvironment is a significant factor that promotes tumor progression [31] and determines the properties of melanoma EVs [32]. EVs can stimulate migration and invasion of metastatic non-invasive melanoma cells [32]; however, the EVs' influence on keratinocytes homeostasis was not studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma growth is accompanied by acidification of the tumor microenvironment to pH ~6.5 instead of ~7.4 in normal conditions [30]. Acidification of the microenvironment is a significant factor that promotes tumor progression [31] and determines the properties of melanoma EVs [32]. EVs can stimulate migration and invasion of metastatic non-invasive melanoma cells [32]; however, the EVs' influence on keratinocytes homeostasis was not studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a high level of ASIC expression in the nervous system, where they are involved in physiological processes such as pain perception, synaptic plasticity, learning, and memory, most ASIC and ENaC subunits are present in different non-excitable tissues, and the channels formed by them can also be implicated in tumor pathogenesis. Our previous results and literature data point on the possible ASIC1 and ENaC expressions in leukemia ( 15 ), glioma ( 16 ), melanoma ( 17 ), breast cancer ( 18 ), and pancreatic ( 19 ), lung ( 3 ), and hepatocellular carcinoma cells ( 20 ), where the ASIC1-containing channels participate in the regulation of cancer cell proliferation, migration, and invasion. In particular, the ASIC1a-containing channels affect the proliferation and migration of lung adenocarcinoma A549 cells induced by extracellular acidosis ( 3 ).…”
Section: Introductionmentioning
confidence: 79%
“…Previously, we showed that the recombinant analogue of mambalgin-2 inhibits the growth of leukemia ( 15 ) and glioma cells ( 16 ) and the growth and migration of melanoma cells ( 17 ). Here, we tested mambalgin-2’s effect on lung adenocarcinoma A549 and Lewis cells, lung transformed WI-38 fibroblasts, and lung normal HLF fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations